THE EFFECT OF USING CROSSWORD PUZZLES ON THE LEARNING OUTCOMES OF FIFTH GRADE STUDENTS AT SD INPRES 12/79 CELLU I - Sudirman Sudirman; Muhammad Awal Nur; Ismawati Ismawati (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This research aims too determine how the use of the Crossword Puzzle media affects the science learning outcomes (IPAS) of fifth-grade students at SD Inpres 12/79 Cellu I, Tanete Riattang Timur Sub-district, Bone Regency, this study employed a quantitative method and a pre-experimental design. A One-Group Pretest-Posttest Design was used. The population consisted of 124 students, with a sample of 21 fifth-grade students selected using cluster random sampling. Data were collected through learning outcome tests administered before and after the use of the Crossword Puzzle media. These data were analyzed using descriptive and inferential statistics. The average pretest score was 50.4, falling into the low category, while the average posttest score was 72.8, categorized as adequate, based on descriptive statistical analysis. The results of the data analysis were tested at a 5% significance level. The calculated t-value was 10.576, greater than the critical t-value of 2.08596. As a result,  is accepted, indicating that the use of Crossword Puzzle media has a significant effect on the science learning outcomes (IPAS) of fifth-grade students at SD Inpres 12/79 Cellu I, Tanete Riattang Timur Sub-district, Bone Regency.